Ensino de artes visuais e o currículo no ensino médio: um estudo em Santa Maria/RS - Marostega, Simone (2006)
This application put it in live of research Craft an Education . produce by PPGE/CE/UFSM. The research has contribute with debate above the teach of the visual craft in the secundary schools. Thus, we used some ways like pather, qualitative, descriptive and critical interpretative. The research by raws, we used trough of the questions, notes, documental analysis, scope and demonstratives. The skills people the went agent teachers that instruction the discipline Visual Craft by secondary instruction, in the public schools an private schools our city Santa Maria/RS. We guide by pather theories acritical, critical an post critical, there are conceptions different behind educational instructions, interaction, know-how and artistics work, social and educational (Appel, 1989; Moreira, 2002; Silva, 1999; Moraes, 1997; Tourinho, 2004). We observed that a great group interview teachers, they develop a pattern in the Visual Craft, with conception critical path, but only copy reproductive, however the models at now, they continue a practical without context critical, with attention to traditional pattern progressive and technicalities. They show a ecletic praxis, these teachers, with evidences acritical, they get several possibilities. In fact that we perceive many works they are notes, the manner organization and discipline alternative. Thus we deduce the history global craft and brazilian, actual, appear behind the knowledge, more interesting on the planes of courses, in the most teachers, are to do they selves, we observation a hempt, only one profit to school teachers and in unusual cases, parents/comunit. The plans are to arrange for trimestrial in public schools and bimestrial and private schools, some those schools they work with two periods in the week: only one ninety minutes. In the investigate we did, half to have a local in these schools to practical craft classes, a few school to have classes in condition to teach Visual Craft and the others schools haven´t or use classes inadequate for this activity. importance facts to stimulate us to punctuate a curriculum in the Visual Craft on the secondary level, a prospect post critical, and the some time to perceive some seeds will be entered a manner that in a few flexibility from curriculum, to knowledge an educational acting. According to our sense perception, it´s necessary give the visibility this curriculum post critical, and show it to teach of Craft. A life mixture a that knowledge each students and teachers, present in this moment post-modern. This believe that only like politics of govern and public with purpose ally continued in or adequate formation, together, with conditions to work (time, space, material) and mean the professional valorize, and the teaching Visual Craft, must finished with curriculum grates that keep enclosed, cutting knowledge and people amplifying than. Visual Craft curriculum staying only one a was connected, heterogeneous, multiplied, non patriotic. A map with a direction, and each teacher will be to choice your turning it, your way, when want will be modify, in your mind, to reorganize, without begin and the end, demarcating but only a destine: the knowledge, the experience in the art.